La gestión del programa de ayuda directa a los más pobres, Juntos y la percepción de las beneficiarias del distrito de Contumazá y caseríos, departamento Cajamarca, 2016. - Alva Castillo, Abel Enmanuel (2018)
The purpose of this study is to make known the experience with the beneficiaries of the Direct Assistance Program for the Poorest in the province of Contumazá, in reference to the perception that these people have regarding their own Program and the people who manage it. ; This will be achieved through bibliographic reviews, formal and informal interviews, home visits, surveys and other control activities carried out; in which it is appreciated that this and other programs require an orderly design and organization with an adequate follow-up. In this context, we are in a process of reform of the Social Programs that the Government wants to promote, which aims to make these efficient to improve the living conditions of the population and reduce poverty. In accordance with the search for efficient use of public resources in government programs, recognizing the need to have an updated diagnosis of social programs and in the context of preventive control, has identified those aspects that represent risks to achieve the objective proposed. With the present investigation we were able to know in depth the reality in which they live, the knowledge and the perception that the beneficiaries of the Program of Direct Assistance to the Poorest have; Two surveys and an in-depth interview were conducted, all to find out the reasons why all the beneficiaries still have a poor quality of life, why said beneficiaries have become more conformist when receiving said bi-monthly incentive, which was applied to 4 beneficiaries. It could be said that many of the beneficiaries have a negative perception of the Program, from the professional point of view, it is clearly evident that the beneficiaries have become accustomed to the Welfare Programs, which do not develop their skills and do not exploit the knowledge that many of them may have; and the annoyance of the beneficiaries was also noted for the political purposes of the Program, which does not always benefit the poorest.